From strategy to innovation strategy: An analysis in colombian companies [De la estrategia a la estrategia de innovación: Un análisis en empresas colombianas] (2016)
This paper presents the relationship between understood as a content that facilitates decision making and strategic management in organizations and its subsequent transformation to a strategy of organizational innovation strategy, taking into account the dynamic capabilities and the three elements of a strategy corporate innovation and competitive national position, technological trajectories and organizational and management processes; through a qualitative research surveyed 262 companies in Colombia was applied in order to identify the level of development of their innovation strategies, key findings show that the strategic direction of investment in R + D + i, It is critical for organizational innovation strategy and lack of management demands greater efforts in organizational planning. There is evidence that companies in the country have been working on projects for knowledge management, creativity, talent and innovation projects, ie are traveling the road to innovation management, which in the medium term may become results Early that generates changes in their production systems and help rethink the strategic direction to preserve the positioning face new competitors.